2021
DOI: 10.1038/s41385-021-00409-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid is a negative regulator of mucosal fibroblast-mediated enhancement of HIV infection

Abstract: The majority of HIV infections are established through the genital or rectal mucosa. Fibroblasts are abundant in these tissues, and although not susceptible to infection, can potently enhance HIV infection of CD4+ T cells. Hyaluronic acid (HA) is a major component of the extracellular matrix of fibroblasts, and its levels are influenced by the inflammatory state of the tissue. Since inflammation is known to facilitate HIV sexual transmission, we investigated the role of HA in genital mucosal fibroblast-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…In this process, virion-incorporated CD44 and HA bound to CD44 are unlikely to contribute to virus capture because mucosal fibroblasts capture HIV-1 even when HIV-1 is produced from 293T cells that do not express CD44. Furthermore, the knockout of HA synthase 2 in mucosal fibroblasts does not affect virus capture efficiency [100], suggesting that HA on the surface of mucosal fibroblasts does not play a major role in trans-infection. Therefore, the molecular mechanisms of mucosal fibroblast-and FRC-mediated trans-infection are distinct.…”
Section: Cd44 Promotes Fibroblastic Reticular Cell-mediated Trans-infectionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this process, virion-incorporated CD44 and HA bound to CD44 are unlikely to contribute to virus capture because mucosal fibroblasts capture HIV-1 even when HIV-1 is produced from 293T cells that do not express CD44. Furthermore, the knockout of HA synthase 2 in mucosal fibroblasts does not affect virus capture efficiency [100], suggesting that HA on the surface of mucosal fibroblasts does not play a major role in trans-infection. Therefore, the molecular mechanisms of mucosal fibroblast-and FRC-mediated trans-infection are distinct.…”
Section: Cd44 Promotes Fibroblastic Reticular Cell-mediated Trans-infectionmentioning
confidence: 98%
“…In addition to FRCs, mucosal fibroblasts also mediate trans-infection [99,100]. In this process, virion-incorporated CD44 and HA bound to CD44 are unlikely to contribute to virus capture because mucosal fibroblasts capture HIV-1 even when HIV-1 is produced from 293T cells that do not express CD44.…”
Section: Cd44 Promotes Fibroblastic Reticular Cell-mediated Trans-infectionmentioning
confidence: 99%
“…It has also been shown that CRISPR/Cas9 technology can increase the function of HIV-infected CD4 + T cells after removing hyaluronic acid from fibroblasts. Hyaluronic acid is the main component of the fibroblast extracellular matrix, and its level is affected by tissue inflammation 55 . The three successfully cured HIV cases suggest that anti-HIV gene therapy based on hematopoietic stem cells (HPSC) can theoretically cure HIV infection.…”
Section: Strategies For Elimination Of Hiv Latent Reservoirsmentioning
confidence: 99%
“…The vaginal mucosa is a squamous epithelium organized in different levels where cells become more differentiated, migrating apically [1]. Here, resident fibroblasts are responsible for the production of hyaluronic acid, thus maintaining hydration of the area [2].…”
Section: Introductionmentioning
confidence: 99%